The mRNA Expression Profile of PD-1 and PD-L1 in Peripheral Blood of Colorectal Cancer Patients - Ajoedi Ajoedi; Muhammad Al Azhar; Siti Nadliroh; Sri Hartini; Rizka Andalusia; Arief Budi Witarto (Indonesian Journal of Cancer, 2019)
Background: Immunotherapy using immune checkpoint inhibitors has currently emerged as an effective treatment for a subset of colorectal cancer (CRC) patients. The roles of PD-1 and PD-L1 expression levels in peripheral blood to predict patient’s response to immune checkpoint inhibitors are not well established. Therefore, we analyzed PD-1 and PD-L1 mRNA expression levels of peripheral blood in Indonesian CRC patients and explored the association with the clinicopathological features.Methods: Peripheral blood of 25 CRC patients and 10 healthy individuals were collected in Dharmais Hospital-National Cancer Center from 2017 to 2018. PD-1 and PD-L1 mRNA expression levels were analyzed using real time PCR. The associations with clinicopathological variables were analyzed with fisher-exact test or chi square test.Results: PD-1 mRNA expression levels were significantly lower in CRC patients compared to healthy individuals (HI) (mean: 0.0015 ± 0.0013 and 0.017 ± 0.010 respectively, p < 0.001). Although PD-L1 mRNA expression levels were lower in CRC patients, the difference was not statistically significant (mean in CRC and HI: 0.021 ± 0.013 and 0.034 ± 0.028 respectively, p = 0.125). The expression of PD-L1 was higher in CRC females compared to males (p = 0.03). The expression levels of PD-L1 were not associated with different ages (p = 0.673), stages (p = 0.298), histological type of colorectal cancer (p=0.852), patient status (p = 1.000), and body mass index (p = 0.514).Conclusions: The mRNA expression levels of PD-1 and PD-L1 were lower in CRC patients compared to healthy controls. Expression of PD-L1 were correlated with sex, but not correlated with ages, stages, histological type of CRC, patient status, and body mass index.